Analisis Yuridis Pengawasan dan Kepastian Hukum Penyelenggaraan Program Makan Bergizi Gratis di Sekolah - Eka Priambodo; Ika Kartika Sari (Universitas Cokroaminoto Yogyakarta, 2026)
The Free Nutritious Meal Program (Program Makan Bergizi Gratis/MBG) is a government policy aimed at improving students’ nutritional quality and fulfilling children’s rights to health and education. However, its implementation has encountered various challenges, particularly food poisoning risks that directly threaten students’ safety. These issues highlight the importance of strengthening supervision and legal certainty in the implementation of the MBG program. This study aims to analyze juridically the supervision and legal certainty of the Free Nutritious Meal Program in preventing food poisoning risks in schools. This research employs a normative legal approach using library research methods by examining statutory regulations, legal principles, and relevant academic literature. The results indicate that although the MBG program is supported by a strong legal foundation, its legal certainty remains inadequate due to the absence of specific technical regulations governing food safety standards, integrated supervision mechanisms, and clear legal responsibility among involved parties. Furthermore, supervision has not been effectively integrated between the central government, local governments, and educational institutions. Therefore, strengthening technical regulations, enhancing cross-sectoral supervision, and clarifying legal accountability are necessary to ensure food safety and protect children’s rights within the implementation of the Free Nutritious Meal Program in schools.